IMPACT OF GOVERNMENT DOMESTIC BONDS ON CAPITAL MARKET GROWTH IN NIGERIA - USMAN, MUSA MUSA; ALHAJI, MOHAMMED LIMAN; ALHASSAN, ABDULKARIM SHAIBU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The Nigerian capital market plays a pivotal role in fostering economic development by mobilizing long-term funds and channeling them into productive investments. As a financial intermediary, it facilitates the flow of resources from surplus units (investors) to deficit units (borrowers), thereby promoting savings, investment, and wealth creation. This study investigates the effect of sovereign government domestic bonds (Federal Government of Nigeria Bonds [FGN Bonds], FGN Savings Bonds, and FGN Sukuk) on the growth of the Nigerian capital market from 2009 to 2024. Using an ex post facto research design, quarterly time-series data were analyzed through the Autoregressive Distributed Lag (ARDL) model to estimate both short-run and long-run relationships. The findings reveal that FGN Bonds, FGN Savings Bonds and FGN Sukuk significantly affect the positive long-term effects on the growth of the Nigerian capital market. The study concludes that sovereign bonds play a critical role in driving the growth and development of the Nigerian capital market, underlining the need for strategic policies to ensure sustainable market expansion. Based on these results, the study recommends strategies to optimize bond issuance, such as addressing short-term disruptions, intensifying awareness campaigns for FGN Savings Bonds and encouraging greater issuance of FGN Sukuk.